The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-87253-4
|View full text |Cite
|
Sign up to set email alerts
|

Making the choice between bioelectrical impedance measures for body hydration status assessment

Abstract: Situational or persistent body fluid deficit (i.e., de- or hypo-hydration) is considered a significant health risk factor. Bioimpedance analysis (BIA) has been suggested as an alternative to less reliable subjective and biochemical indicators of hydration status. The present study aimed to compare various BIA models in the prediction of direct measures of body compartments associated with hydration/osmolality. Fish (n = 20) was selected as a biological model for physicochemically measuring proximate body compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In addition, the agerelated sarcopenia was included in the International Classification of Diseases (ICD-10-CM) with the code M62.84. Although in 2021 there are at least three major consensus groups publishing about sarcopenia (the European Working Group on Sarcopenia in Older People, EWGSOP, the European Society for Clinical Nutrition and Metabolism Special Interest Group, ESPEN-SIG, and the International Working Group on Sarcopenia, IWGS), there is still a lack of worldwide agreement right on the definition of sarcopenia [3][4][5]. Probably, the most widely accepted and used definition of sarcopenia is from the European Working Group (EWGSOP, the Sarcopenia Working Group) encompassing both the presence of low muscle mass and low muscle function (strength and performance) [3].…”
Section: Clinical Relevance Of Sarcopenia and The Endocrine Function Of The Skeletal Musclementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the agerelated sarcopenia was included in the International Classification of Diseases (ICD-10-CM) with the code M62.84. Although in 2021 there are at least three major consensus groups publishing about sarcopenia (the European Working Group on Sarcopenia in Older People, EWGSOP, the European Society for Clinical Nutrition and Metabolism Special Interest Group, ESPEN-SIG, and the International Working Group on Sarcopenia, IWGS), there is still a lack of worldwide agreement right on the definition of sarcopenia [3][4][5]. Probably, the most widely accepted and used definition of sarcopenia is from the European Working Group (EWGSOP, the Sarcopenia Working Group) encompassing both the presence of low muscle mass and low muscle function (strength and performance) [3].…”
Section: Clinical Relevance Of Sarcopenia and The Endocrine Function Of The Skeletal Musclementioning
confidence: 99%
“…Although in 2021 there are at least three major consensus groups publishing about sarcopenia (the European Working Group on Sarcopenia in Older People, EWGSOP, the European Society for Clinical Nutrition and Metabolism Special Interest Group, ESPEN-SIG, and the International Working Group on Sarcopenia, IWGS), there is still a lack of worldwide agreement right on the definition of sarcopenia [3][4][5]. Probably, the most widely accepted and used definition of sarcopenia is from the European Working Group (EWGSOP, the Sarcopenia Working Group) encompassing both the presence of low muscle mass and low muscle function (strength and performance) [3]. In 2018, the European Working Group on Sarcopenia in Older People met again (EWGSOP2) to update the original definition of sarcopenia introducing new scientific and clinical insights developed in the last 10 years [4].…”
Section: Clinical Relevance Of Sarcopenia and The Endocrine Function Of The Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Arens et al showed that the hands and feet were considerably colder than the head and arms in a cold environment, and thus vasoconstriction was the strongest [45]. These different physiological changes in distinct body parts have been shown to affect the biological impedance measurement [46][47][48]. Therefore, the choice of body part is expected to influence the biometric authentication performance (e.g., the peripheral end of extremities such as fingers, or parts of the body close to the core such as the upper limb).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the genetics of the three-compartment model of body composition will provide new insights into the shared heritability of and inter-connection between fat, lean and bone traits. Moreover, the majority of research has derived estimates of fat and lean mass from bio-electrical impedance analysis, which has inflexible hydration assumptions and is unable to assess bone mass ( 7 ). While dual energy X-ray absorptiometry (DXA) is the gold standard for assessing the three-compartment model of body composition, the high cost and exposure to radiation has largely precluded application in a large population cohort ( 8 ).…”
Section: Introductionmentioning
confidence: 99%